The Systemic Role of Monopolistic Enterprises in the Russian Insurance Market - Oborin M.S.; Rainkhardt R.O. (Управленец, 2018)
The article discusses the role of monopolistic enterprises in the Russian insurance market. The methodological basis of the paper is the system and situational approaches aimed at assessing insurance as a stabilizing factor for industries that are of priority importance for the state. The information base of the study is the statistics on the insurance market and expert forecasts about prospects and trends in its development. The authors perform the analysis using the case of the leader in industry insurance – AO “Atomic Insurance Broker”; we also study the effect for the specialized nuclear enterprises and justify the role in the sector’s economic stability. The research results demonstrate that the monoindustry insurer exerts a positive effect on the Russian economy, which results in reducing risks, covering losses and improving the quality of crisis management. We conclude that the special features of the Russian insurance market are attributed to specific problems of socio-economic development of the country and a rise in structural economic risks. Our analysis shows that, if there is a monopolistic insurer in the industry, a growing impact of the state serves as a stabilizing factor that positively affects the interrelated economic sectors.